Perfusion-Weighted Imaging–Derived Collateral Flow Index is a Predictor of MCA M1 Recanalization after IV Thrombolysis - Nicoli, F.; Lafaye de Micheaux, P.; Girard, N. (American Journal of Neuroradiology, 2013)
BACKGROUND AND PURPOSE: Recent studies highlight the role of CC in preserving ischemic penumbra. Some authors suggested the quality of CC could also impact recanalization. The purpose of this study is to test this hypothesis in patients who were treated with IV thrombolysis for MCA-M1 occlusion. MATERIALS AND METHODS: A normalized index derived from Tmax maps (MR-PWI) was defined to quantify the CC deficit (nCCD) in 64 patients with stroke who underwent IV thrombolysis. Correlations between nCCD and parameters that may be altered by CC quality were tested (baseline NIHSS, volume of diffusion abnormalities, modified Rankin Scale at 3 months). The correlation between baseline nCCD and MCA-M1 recanalization rate at 24 hours was tested. RESULTS: The nCCD is significantly correlated with NIHSS and with lesional volume (Pearson correlation test, positive correlations, respectively, 0.40, 0.57; P = .00089, P = 8.7e-07). The nCCD also has a significant predictive value on the full recanalization at 24 hours that decreases as TTT increases (logistic regression, P = .021). Furthermore, among patients who were treated within 3 hours, nCCD and recanalization are significantly correlated (correlation ratio test, eta2 = 0.23, P = .0023): Patients who did not achieve full recanalization have significantly higher nCCD than fully recanalized patients (Mann-Whitney U test, P = .007). In addition, the probability of full recanalization decreases as the nCCD increases (P = .021). nCCD (OR 0.988, 95% CI 0.977–0.999, P = .042) and full recanalization at 24 hours (OR 4.539, 95% CI 1.252–16.456, P = .021) are independent predictors of functional independence at 3 months. CONCLUSIONS: The nCCD index is a predictor of full MCA-M1 recanalization in patients treated with IV thrombolysis. AIFarterial input functionCCcollateral circulationCIconfidence intervalnCCDnormalized collateral circulation deficitTmaxtime-to-maximum of the flow-scaled residue functionTTTtime-to-treatment (equivalent to onset-to-needle time)